2021
DOI: 10.3390/ma14216602
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Nano/Micro Bimodal Aluminum Powder by Electrical Explosion of Wires

Abstract: Electrical explosion of aluminum wires has been shown to be a versatile method for the preparation of bimodal nano/micro powders. The energy input into the wire has been found to determine the relative content of fine and coarse particles in bimodal aluminum powders. The use of aluminum bimodal powders has been shown to be promising for the development of high flowability feedstocks for metal injection molding and material extrusion additive manufacturing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…The positive effect of using bimodal powders obtained by mixing micro-and nanoparticles when preparing the bimodal feedstocks has also been shown by many authors [8,10,17,19,22,[32][33][34] and in our recent study [28,35]. Meanwhile, an increase in the bimodal feedstock viscosity with an increase in the content of nanoparticles above the optimal value was noted by Oh J.W.…”
Section: The Powder-polymer Feedstock Characterizationsupporting
confidence: 73%
See 1 more Smart Citation
“…The positive effect of using bimodal powders obtained by mixing micro-and nanoparticles when preparing the bimodal feedstocks has also been shown by many authors [8,10,17,19,22,[32][33][34] and in our recent study [28,35]. Meanwhile, an increase in the bimodal feedstock viscosity with an increase in the content of nanoparticles above the optimal value was noted by Oh J.W.…”
Section: The Powder-polymer Feedstock Characterizationsupporting
confidence: 73%
“…Ti-Al bimodal powders were obtained by the EEW method using a setup reported previously [26][27][28]. Titanium and aluminum wires with a metal content of 99.9% were used in the experiments to obtain bimodal powders consisting of Ti-Al micro-and nanoparticles.…”
Section: Preparation Of Powdersmentioning
confidence: 99%
“…In present paper a polymer melt containing bimodal particles [ 7 ] is studied. According to the Einstein's dependence of solution viscosity on the concentration of suspended particles [ 31 ] it becomes: where φ – volume fraction of the dispersed phase; α – coefficient depending on the shape of the particles.…”
Section: Mathematical Model Of Flow In Materials Extrusion Technologymentioning
confidence: 99%
“…Another approach, which, however, does not completely exclude ignition during printing, is filling the thermoplastic polymer filament with solid HEM particles [ 6 ]. Bimodal metal powder, which exhibits high fluidity, can be a promising high-energy constituent material for extrusion additive manufacturing [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…3. The research results demonstrated that as current pulse amplitude is growing, the sizes of generated drops move towards submicron area, and nanoparticles may be observed in the dispersion products [15].…”
mentioning
confidence: 92%